Instructional design in EFLT. A challenge and an innovation in teaching and learning english - Bonilla Tenesaca, Josué (2023)
Many instructional design (ID) methods are elaborated to encompass diverse learning problems in different spheres of human activity. Thus, English Language teaching requires innovations and the conscientious application of ID theories; therefore, it is the purpose of this paper to share important issues on ID, which may lead to the redesign of English classes with the application of action/classroom research, one of its cornerstones, which may bring about progress, improvements and facilitation of English learning. The procedures used were the analysis, interpretation, and design of different scientific materials related with the application of ID principles, teaching/learning strategies, students’ profiles, and criteria of CEFR, which may lead to achieving satisfaction of the students´ needs in the different educational sub-systems of Ecuador.